Making Visible HTLV Infection in a Non-endemic Area of Argentina - Simioli, Federico R.; Bouzas, Maria B.; Mijalovsky, Dana; Pineda, Maria V.; Mammana, Lilia; Mangano, Andrea; Orduna, Tomas A. (Frontiers in Medicine, 2022)
In Argentina, HTLV-1 infection has been documented mainly among blood banks with prevalence around 0.02-0.046 % for Buenos Aires city, 0.8% for the northeast and 1% for the northwest; both areas are considered endemic for HTLV-2 and 1 respectively. Policies and specific guidelines for testing blood donors for HTLV are included since 2005. Screening for antibodies is performed at blood banks and confirmatory testing is performed at reference laboratories. There are still no specific recommendations neither for the assistance of communities and individuals affected nor referral to specialized clinics on the HTLV infection. In 2016 as a strategy of intervention we opened a specialized clinical attendance in a referral infectious diseases public hospital, for the comprehensive approach of HTLV patients, offering follow-up and counseling for patients and their families for the early diagnosis of HTLV-1/2 and related diseases. During the study, 124 patients with presumptive HTLV positive diagnosis from blood bank, symptomatic patients, relatives, and descendents visited the unit. A total of 46 patients were HTLV positive (38 HTLV-1 and 8 HTLV-2). Nine patients were symptomatic (2ATLL – 7 HAM/TSP). All HTLV-1 and -2 patients were offered to study their relatives. Two out of 37 (5.4%) descendants tested were positive for HTLV-1. Sexual partners were studied; among 6/11 couples (54.5%) were found positive (5 HTLV-1 and 1 HTLV-2). Other relatives including mothers (1/2) and siblings (1/ 6) were positive for HTLV-1. According to the place of birth among HTLV-1 carriers, 58% were born in an endemic area or in countries where HTLV infection is considered endemic while for HTLV-2 carriers, 12.5% were born in an endemic area of Argentina. Proviral load was measured in all HTLV-1 patients being higher in symptomatic compared to asymptomatic carriers. Two pregnant women were early diagnosed during their puerperium and breastmilk replacement by formula-fed and inhibition of lactation was indicated. Our study provides tools for a multidisciplinary approach of the infection, and reinforces the importance of having specialized clinical units in neglected diseases such as HTLV for counseling, clinical and laboratory follow-up, and providing useful information for patients for self-care and that of their families.